Stress Relief: The Ultimate Teen Guide - Powell, Mark (Rowman & Littlefield Publishers, 2007)
Today's teens are dealing with adult issues and problems that previous generations did not encounter. With little power to control or to affect outcomes, many teens feel overwhelmed, making stress and stress-related problems widespread among today's young people. Stress Relief: The Ultimate Teen Guide makes eliminating stress an art form. Written in a style that appeals to a teen audience, this accessible volume is not about managing stress, but rather about preventing and avoiding it—and eliminating the feelings it causes.